A CASE FOR INDUSTRIAL POLICY? FORECAST RESULTS FROM A DISAGGREGATED BOP-CONSTRAINED GROWTH MODEL FOR BRAZILIAN ECONOMY (2016-2025) - Cryslãine Flavia da Silva Rodrigues; André Luís Cabral de Lourenço (Revista de Economia Contemporânea, 2021)
ABSTRACT The article aimed to forecast the Brazilian economy’s growth potential in the 2016-2025 period, assuming the absence of changes in industrial policy. It is based on a formal growth model constrained by the balance of payments (BOP) developed by the authors and disaggregated into three sectors (farming, industry, and services). All its parameters were econometrically estimated, including those of the world economy relevant to the Brazilian economy’s performance. Assuming that the current macroeconomic management “tripod” was maintained in the country, the basic interest rate and exchange rate policy were calibrated to generate the maximum growth rate allowed by the external constraint compatible with the maintenance of inflation in target each year. Forecasts were also made about the performance of the three sectors’ key variables, resulting from such calibration. Forecasted potential GDP and productivity growth were low (even by recent historical standards) and decreasing over time, with slower growth in the industrial sector than in other ones. The results revealed the critical importance of the industrial sector for such performance, suggesting that an efficient industrial policy could significantly increase the Brazilian economy’s growth potential.